Heart transplant recipient patient with COVID‐19 treated with tocilizumab. Issue 6 (10th July 2020) - Mattioli, Massimo; Fustini, Elisa; Gennarini, Silvia
Abstract: A heart transplant 62‐year‐old patient referred for coronavirus‐19 disease (COVID‐19) pneumonia. At admission, he was febrile, tachypnoeic, and mild hypoxic with dry cough; during hospitalization, a diffuse morbilliform skin rash appeared. He was treated with tocilizumab with symptoms improvement, without a complete pulmonary function recovery. Skin rash, highly suggestive for COVID‐19 cutaneous involvement, persisted for ten days despite tocilizumab administration.